Development of cell-culture modified living goat-pox vaccine - AGRAWAL, S K; PAL, J K; SOMAN, J P (The Indian Journal of Animal Sciences, 2013)
An attempt was made to serially cultivate goat-pox virus 'Ranchi' strain in kid kidney cell-cultures to evolve live virus vaccine for immunoprophylaxis. The strain was isolated from the Chotanagpur region. The virus at 50th passage when subjected to infectivity titration did not produce generalization. It was innocuous in safety trial when inoculated in a dose of 10 000 TCID50 per goat intradermally. Ten goats immunized withÂ  1000 TCID50 dose developed only macular stage at the local site. They withstood challenged infection on day 23 post-vaccination and did not spread the virus to in-contacts. The cytopathic study indicated that the virus retained its original replicative behaviour.